Transcriptome-Wide Map of N6-Methyladenosine Methylome Profiling in Human Bladder Cancer - Li, Aolin; Gan, Ying; Cao, Congcong; Ma, Binglei; Zhang, Quan; Zhang, Qian; Yao, Lin (Frontiers in Oncology, 2021)
N6-Methyladenosine (m6A) is the most widespread internal RNA modification in several species. In spite of latest advances in researching the biological roles of m6A, its function in the development and progression of bladder cancer remains unclear. In this study, we used MeRIPty -55-seq and RNA-seq methods to obtain a comprehensive transcriptome-wide m6A profiling and gene expression pattern in bladder cancer and paired normal adjacent tissues. Our findings showed that there were 2,331 hypomethylated and 3,819 hypermethylated mRNAs, 32 hypomethylated and 105 hypermethylated lncRNAs, and 15 hypomethylated and 238 hypermethylated circRNAs in bladder cancer tissues compared to adjacent normal tissues. Furthermore, m6A is most often harbored in the coding sequence (CDS), with some near the start and stop codons between two groups. Functional enrichment analysis revealed that differentially methylated mRNAs, lncRNAs, and circRNAs were mostly enriched in transcriptional misregulation in cancer and TNF signaling pathway. We also found that different m6A methylation levels of gene might regulate its expression. In summary, our results for the first time provide an m6A landscape of human bladder cancer, which expand the understanding of m6A modifications and uncover the regulation of mRNAs, lncRNAs, and circRNAs through m6A modification in bladder cancer.